2019
DOI: 10.1016/j.ophtha.2019.04.038
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic and Clinical Findings in a Large Cohort of Chinese Patients with Suspected Retinitis Pigmentosa

Abstract: Purpose: To characterize the genetic landscape of patients with suspected retinitis pigmentosa (RP) in the Chinese population.Design: Cohort study.Participants: A total of 1243 patients of Chinese origin with clinically suspected RP and their available family members (n ¼ 2701) were recruited.Methods: All patients and available family members were screened using multigene panel testing (including 586 eye disease-associated genes), followed by clinical variant interpretation.Main Outcome Measures: Diagnostic yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 36 publications
4
83
0
Order By: Relevance
“…7 Also, a recent study reporting findings from 1243 IRD patients of Chinese origin reported a diagnostic yield of 72% (n = 1243). 35 Overall, these comparisons suggest that the likelihood of a genetic test identifying a molecular diagnosis are linked to (1) the current state of knowledge of the genetic architecture of the patient's condition (e.g., higher for albinism and IRD than for cataract and ASD); (2) the pretest probability of the patient having a penetrant monogenic disorder (typically higher for bilateral disease, when there is relevant family history, for specific wellrecognized clinical presentations and/or for early childhood onset conditions). 35,36 Like any other medical interventions, diagnostic genetic tests should be thoroughly evaluated before their introduction into routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…7 Also, a recent study reporting findings from 1243 IRD patients of Chinese origin reported a diagnostic yield of 72% (n = 1243). 35 Overall, these comparisons suggest that the likelihood of a genetic test identifying a molecular diagnosis are linked to (1) the current state of knowledge of the genetic architecture of the patient's condition (e.g., higher for albinism and IRD than for cataract and ASD); (2) the pretest probability of the patient having a penetrant monogenic disorder (typically higher for bilateral disease, when there is relevant family history, for specific wellrecognized clinical presentations and/or for early childhood onset conditions). 35,36 Like any other medical interventions, diagnostic genetic tests should be thoroughly evaluated before their introduction into routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…In the Spanish, Chinese, and German cohorts, which only comprised RP cases, an X-linked pattern of inheritance among the solved cases was observed in 7.9%, 11%, and 12.1%, respectively (Birtel et al, 2018;Gao et al, 2019;Martin-Merida et al, 2019). In contrast, X-linked cases constitute 19.2% of solved patients with RP in our cohort.…”
Section: Genes and Mutation Spectrummentioning
confidence: 49%
“…Diagnostic rates varied according to the disease type ( (Carss et al, 2017;Dockery et al, 2017;Jespersgaard et al, 2019;Sharon et al, 2020;Stone et al, 2017). In addition, for comparison purposes, we focused on two studies that investigated large cohorts of patients with RP in the Spanish and Chinese populations (Gao et al, 2019;Martin-Merida et al, 2019), respectively, and a small RP cohort study performed in the German population (Birtel et al, 2018). (2018) have analyzed 116 patients with RP.…”
Section: Molecular Diagnosis Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherited retinal dystrophies (IRDs) are a clinically and genetically heterogenous group of diseases with an estimated prevalence of 1 in 3,000 individuals. [8] Despite some common ground, genetic pro les vary considerably among regions and ethnic groups, [9][10][11][12][13][14][15][16] thus highlighting the importance of obtaining reference population-based data. The presence of founder mutations may greatly contribute for these differences, as observed in a large Israeli population.…”
Section: Introductionmentioning
confidence: 99%